Proceedings of the 2007 Inaugural International Conference on Distributed Event-Based Systems 2007
DOI: 10.1145/1266894.1266917
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomy for denial of service attacks in content-based publish/subscribe systems

Abstract: Denial of Service (DoS) attacks continue to affect the availability of critical systems on the Internet. The existing DoS problem is enough to merit significant research dedicated to analyzing and classifying DoS attacks in the Internet context. However, no such research exists for DoS attacks in the domain of Content-based Publish/Subscribe (CPS) systems despite CPS being at the forefront of business process execution, application integration, and event processing applications. This can be attributed to the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In the field of publish/subscribe systems, Wun et al [21] present a taxonomy for a specific type of attack against such kind of systems, namely the Denial of Service (DoS). In particular, the authors describe two key characteristics of DoS attacks in the context of pub/sub systems: localization and transmission.…”
Section: Related Workmentioning
confidence: 99%
“…In the field of publish/subscribe systems, Wun et al [21] present a taxonomy for a specific type of attack against such kind of systems, namely the Denial of Service (DoS). In particular, the authors describe two key characteristics of DoS attacks in the context of pub/sub systems: localization and transmission.…”
Section: Related Workmentioning
confidence: 99%
“…Pub/sub networks are working differently from the IP network, but still, denial‐of‐service (DoS) attacks are possible. In , a first attempt is presented to classify DoS attacks for this type of network. This work introduced a very useful taxonomy of the DoS attacks in pub/sub systems.…”
Section: Networking Security In the Network Of The Futurementioning
confidence: 99%
“…The current Internet is continuously threatened by Denial of Service (DoS) attacks. Wun et al were the first that identified and classified this kind of attacks in content based publish/subscribe networks [19]. Interestingly enough, all kinds of attacks identified are based on the rendezvous network; the attackers may flood the rendezvous network with publications, causing the creation of an intolerable number of notifications towards subscribers, or if the rendezvous network allows parameterized subscriptions-e.g., all publications that concern Future Internet published between 2007 and 2009-attackers may use complex expressions and consume the resources of the rendezvous nodes.…”
Section: Security Threatsmentioning
confidence: 99%